Comparison of early vs. routine removal of abdominal drainage tube after laparoscopic appendectomy for perforated appendicitis: a retrospective cohort study - He, Jun; Qian, Gang; Mao, Yefei; Gao, Lei (Frontiers in Surgery, 2025)
BackgroundThe utility of abdominal drainage is common in laparoscopic appendectomy (LA) for acute appendicitis with perforation to prevent postoperative complications, such as intraabdominal abscess (IAA) and stump fistula. Nevertheless, the drain tube placement is considered to be associated with postoperative IAA formation in cases of complicated appendicitis. Our study aims to determine whether early removal of abdominal drainage tube after LA can improve prognosis for patients with perforated appendicitis.MethodsA total of 182 patients who underwent abdominal drainage tube placement during LA due to acute appendicitis with perforation were divided into experimental group and control group by random number table method, including 87 patients in the experimental group and 95 patients in the control group. Patients in the experimental group had their abdominal drainage tube removed within 48 h after surgery. Patients in the control group removed the drainage tube after 48 h routinely. Variables of demographic and clinical characteristics of these patients between the two groups were analyzed. Postoperative outcomes, including overall complications, IAA, superficial surgical site infection (SSI), stump fistula, ileus, bleeding, postoperative length of stay (LOS), hospitalization costs and readmission to hospital, were compared.ResultsThese two groups were similar regarding demographic and perioperative clinical characteristics like age, sex, duration of symptoms and hematological examination indicators (P > 0.05). Although there was no significant difference in superficial SSI and ileus between the two groups (P > 0.05), patients in the experimental group was associated with a lower rate of overall complications (3.4% vs. 17.9%, P = 0.002), declined incidence of IAA (3.4% vs. 11.6%, P = 0.040), a shorter LOS [4 (4,4) vs. 6 (5,6) days, P < 0.001] and less hospitalization costs [9,705 (8,621−10,402) vs. 10,851 (9,704−11,752) CNY, P < 0.001] compared with patients in the control group. No stump fistula and intraabdominal bleeding occurred in both groups. There was no significant difference in readmission rate within 30 days after surgery between the two groups (P = 0.684).ConclusionsIt is safe and effective to remove abdominal drainage tube within 48 h after LA for patients with perforated appendicitis. This approach can accelerate the recovery time, decline the incidence of IAA and reduce hospitalization costs.